PDK1 is a potential therapeutic target against angiosarcoma cells. Issue 1 (April 2015) - Wada, Makoto; Horinaka, Mano; Yasuda, Shusuke; Masuzawa, Mikio; Sakai, Toshiyuki; Katoh, Norito
Highlights The PI3K inhibitor and mTOR inhibitor induced G1 cell cycle arrest. Cyclin D levels were decreased by knockdown of PDK1, not by AKT inhibitor. The knockdown of PDK1 inhibited colony formation than the mTOR inhibitor.